Occipital Lobe Epilepsy With Ictal Fear: Evidence From a Stereo-Electroencephalography (sEEG) Case - Wang, Jing; Wang, Qian; Wang, Mengyang; Luan, Guoming; Zhou, Jian; Guan, Yuguang; Yan, Zhaofen (Frontiers in Neurology, 2018)
Ictal fear—a relatively rare phenomenon—is a semiological characteristic of epilepsy. Most patients with epilepsy with ictal fear have an epileptic zone in the mesial temporal lobe, which is the classical brain area involved in emotion processing. Herein, we report a case of epilepsy with ictal fear as the first manifestation in a 10-year-old boy. All noninvasive evaluation including scalp video electroencephalography (EEG), magnetic resonance imaging (MRI), and positron emission tomography/computed tomography (PET-CT) suggested a possible lesion in the left posterior brain region. Stereo-electroencephalography (sEEG) results showed high frequency direct current shift in the left occipital lobe 1 s before the fear manifestation which preceded in 12 s the discharge in the amygdala. This case highlights the epileptic network hypothesis which suggested occipital cortex may play an important role in the early emotional network independently of amygdala activation.